2015
DOI: 10.1002/mawe.201400386
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitriding on corrosion resistance of martensitic X17CrNi16‐2 stainless steel

Abstract: Nitriding increases surface hardness and improves wear resistance of stainless steels. However, nitriding can sometimes reduce their corrosion resistance. In this paper, the influence of nitriding on the corrosion resistance of martensitic stainless steel was investigated. Plasma nitriding at 440°C and 525°C and salt bath nitrocarburizing were carried out on X17CrNi16-2 stainless steel. Microhardness profiles of the obtained nitrided layers were examined. Phase composition analysis and quantitative depth profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…However, it was restricted to the composite layer (50 µm). Similar hardened layers (1200 HV 0.05 /11.77 GPa, 30 µm) were obtained by Cajner et al [13] in an X17CrNi16-2 (martensitic) steel but with an unwanted core softening, caused by tempering effect. Contrasting with as-nitrided samples, SHTPN led to a surface hardness of 580 HV (5.69 GPa), which is almost constant along the first 200 µm.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, it was restricted to the composite layer (50 µm). Similar hardened layers (1200 HV 0.05 /11.77 GPa, 30 µm) were obtained by Cajner et al [13] in an X17CrNi16-2 (martensitic) steel but with an unwanted core softening, caused by tempering effect. Contrasting with as-nitrided samples, SHTPN led to a surface hardness of 580 HV (5.69 GPa), which is almost constant along the first 200 µm.…”
Section: Resultssupporting
confidence: 82%
“…As can be seen, the precipita- tion of chromium nitrides in the nitrided sample, confirmed by the XRD patterns, resulted in a less noble corrosion potential and an increase of current density, which consequently led to a higher corrosion rate. Cajner et al [13] observed the same corrosion behavior in plasma nitrided martensitic steel and attributed it to chromium nitride precipitation. Despite changing from ferrite to nitrogen martensite, the corrosion behavior shows small changes if compared with untreated steel, except for a reduction of pitting corrosion potential.…”
Section: Resultsmentioning
confidence: 76%
“…There are literature studies on the corrosion and wear properties of nitrided layers on martensitic stainless steels hardened by carbon [ 7 , 14 , 15 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and 17-4 PH [ 24 , 39 ] steel, but the data on the performance of nitrided Nanoflex steel are practically unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Nitriding plays a central role in this scenario, giving more versatility to the nitrogen content that can be added to austenitic stainless steels [18]. Plasma nitriding has gained increased technological relevance as a large-scale processing method to achieve nitrogen-rich stainless steel surfaces [19][20][21]. Recently, electrochemical nitriding has emerged as an alternative route to incorporate nitrogen into the surface of stainless steels [22].…”
Section: Introductionmentioning
confidence: 99%